Angiotensin I-converting Enzyme (ACE) Inhibitory Activity of ACE Inhibitory Peptides Produced during the Fermentation of Pigeon Pea (Cajanus cajan) Tempe - Suci Apsari Pebrianti; Muhammad Nur Cahyanto; Retno Indrati (Indonesian Food and Nutrition Progress, 2019)
Fermentation products are common sources of angiotensin I-converting enzyme (ACE) inhibitory peptides used for hypertension treatment. This research investigated the effect of fermentation time on the ACE inhibitory activity produced during the fermentation of pigeon pea tempe and aimed to determine the optimal fermentation time to obtain pigeon pea tempe with the highest ACE inhibitory activity. Seeds were inoculated with Raprima® (0.02% w/w) containing Rhizopus oligosporus spores and fermented for 0-96 h. Protein pattern, degree of hydrolysis (DH), soluble protein content and ACE inhibitory activity were observed during fermentation. The result from SDS-PAGE shows that protein hydrolysis occurred after 12 h fermentation, marked by the appearance and greater intensity of protein bands with low-molecular-weight (60 kDa). An increase in DH and soluble protein content were detected during the fermentation and reached a maximum of 23.99% and 3.15 mg mL -1 at 96 h fermentation, respectively. The ACE inhibitory activity increased with fermentation time and pigeon pea tempe fermented for 48 h (76.14%) has the highest ACE inhibitory activity with IC 50 values of 0.65 mg mL -1 . It could be concluded that the optimal fermentation time to obtained pigeon pea tempe with the highest ACE inhibitory activity is for 48 h of fermentation.